Estudio de factibilidad para la creación de una planta de aprovechamiento de los residuos orgánicos generados en las plazas de mercado y producción de abonos orgánicos en Santiago de Cali. (2011)
This work corresponds to a feasibility study for creating a company dedicated to the use of organic solid waste generated in the market places of the city of Santiago de Cali. Usually treat the waste arising from processing and marketing of vegetables.To determine the quantities of waste generated research was conducted in the six (6) market places of the city to meet the environmental problems they pose, and to identify the quantities generated. After knowing the problem of these places were identified guidelines that have legal standards for organic waste management, and consulted particularly the Waste Management Plan Solid Cali; PGIRS. Based on the problem of market places and the provisions of PGIRS, we proceeded to design a system of exploitation, which is based on a plant that uses waste to produce organic fertilizer or compost. The project is characterized by requiring an investment of $ 12,768,385,500, which is budgeted to buy the land and machinery necessary to stop initiating operations. In the first phase of the project will create 46 jobs. Organizational structure was designed to establish a management model according to the demands of the project, facilitating the processes of communication and decision-making. Also made marketing strategies to get the product into the market in Cali and Valle del Cauca. You raised the strategy to generate an image of social and environmental responsibility with the activity of the company and its product.